2016
DOI: 10.1371/journal.pone.0162549
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehogs and Mustelid Species: Major Carriers of Pathogenic Leptospira, a Survey in 28 Animal Species in France (20122015)

Abstract: Human leptospirosis is a zoonotic and potentially fatal disease that has increasingly been reported in both developing and developed countries, including France. However, our understanding of the basic aspects of the epidemiology of this disease, including the source of Leptospira serogroup Australis infections in humans and domestic animals, remains incomplete. We investigated the genetic diversity of Leptospira in 28 species of wildlife other than rats using variable number tandem repeat (VNTR) and multispac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 33 publications
6
41
0
Order By: Relevance
“…Ayral et al. () recommended a combination of PCR and rrs gene typing to improve outcomes of prevalence studies in wild animals, and in the present study that approach could successfully demonstrate the variability of circulating species among Atlantic Forest mammals.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Ayral et al. () recommended a combination of PCR and rrs gene typing to improve outcomes of prevalence studies in wild animals, and in the present study that approach could successfully demonstrate the variability of circulating species among Atlantic Forest mammals.…”
Section: Discussionmentioning
confidence: 60%
“…There are scarce reports on leptospiral characterization from wildlife. In Europe, the circulating species are L. interrogans , L. kirschneri and L. borgpetersenii (Arent, Gilmore, San‐Miguel Ayanz, Neyra, & García‐Peña, ; Ayral et al., ; Fischer et al., ; Obiegala et al., ), and a recent study in Brazil reported L. interrogans , L. santarosai and L. borgpertesenii (Fornazari et al., ). To our knowledge, L. noguchii strains had never been reported on wildlife.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an amplifiat of between 300 and 400 bp on 1.5% agarose gel after migration is considered a positive signal. This method has been validly used in previous studies to explore the renal carrier state in a very large variety of wildlife mammals (Ayral et al ).…”
Section: Methodsmentioning
confidence: 99%
“…According to observations recorded in the French Leptospira laboratory in Lyon, titres higher than 1:100 have been considered positive for humans and all animal species. This method has been validly used in previous studies to explore the renal carrier state in a very large variety of wildlife mammals (Ayral et al 2016).…”
Section: Serological Studiesmentioning
confidence: 99%